A Computationally Efficient Feasible Sequential Quadratic Programming Algorithm - Lawrence, Craig T.; Tits, André L. (SIAM journal on optimization, 2001)
A sequential quadratic programming (SQP) algorithm generating feasible iterates is described and analyzed. What distinguishes this algorithm from previous feasible SQP algorithms proposed by various authors is a reduction in the amount of computation required to generate a new iterate while the proposed scheme still enjoys the same global and fast local convergence properties. A preliminary implementation has been tested and some promising numerical results are reported.